Organizational Effectiveness and the Voluntary Organization - Webb, Ronald J. (Academy of Management Journal, 1974)
Although researchers have studied organizational effectiveness, the voluntary organization has been excluded. This study identifies organizational characteristics which act as determinants of effectiveness of voluntary church organizations. The findings differ markedly from earlier studies of organizational effectiveness and indicate that organization development in voluntary organizations may need to undergo rethinking.